Nanotwin's formation and growth in an AlCoCuFeNi high-entropy alloy. (15th March 2016) - Yu, P.F.; Cheng, H.; Zhang, L.J.; Zhang, H.; Ma, M.Z.; Li, G.; Liaw, P.K.; Liu, R.P.
Abstract: Nanotwins were formed in the AlCoCuFeNi high-entropy alloy produced by melt-spinning. The Cu-rich nanotwins have a face-centered-cubic (FCC) structure diffused in the ordered body-centered-cubic (B2) matrix. The nanotwins decompose from the matrix with the K–S crystallographic relationship: {111}FCC  ∥ {110}B2 and < 110 >FCC  ∥ < 111 >B2 . After annealing, the spherical nanotwins grow into rodlike grains. The growth direction is parallel to the {111} twin planes of the FCC phase. The hardness and elastic modulus change with the twin size, which is tested by nanoindentation. This study deepens the fundamental understanding of the phase transition in HEAs. Graphical abstract: The melt-spun equiatomic AlCoCuFeNi HEA with a large amount of nanoscaled twins about 20 nm disperses uniformly in the matrix. And these nanotwins keep the K–S crystallographic relationship: {111}FCC  ∥ {110}B2, and < 110 >FCC  ∥ < 111 >B2 .